Numerical Investigation of Countermeasure Effects on Overland Flow Hydrodynamic and Force Mitigation in Coastal Communities - Hai Van Dang; Sungwon Shin; Eunju Lee; Hyoungsu Park; Jun-Nyeong Park (한국해양공학회지, 2022)
Coastal communities have been vulnerable to extreme coastal flooding induced by hurricanes and tsunamis. Many studies solely focused on the overland flow hydrodynamic and loading mechanisms on individual inland structures or buildings. Only a few studies have investigated the effects of flooding mitigation measures to protect the coastal communities represented through a complex series of building arrays. This study numerically examined the performance of flood-mitigation measures from tsunami-like wave-induced overland flows. A computational fluid dynamic model was utilized to investigate the performance of mitigation structures such as submerged breakwaters and seawalls in reducing resultant forces on a series of building arrays. This study considered the effects of incident wave heights and four geometrically structural factors: the freeboard, crest width of submerged breakwaters, and the height and location of seawalls. The results showed that prevention structures reduced inundation flow depths, velocities, and maximum forces in the inland environment. The results also indicated that increasing the seawall height or reducing the freeboard of a submerged breakwater significantly reduces the maximum horizontal forces, especially in the first row of buildings. However, installing a low-lying seawall closer to the building rows amplifies the maximum forces compared to the original seawall at the shoreline.